ANALYZING THE CRITICAL DISCOURSE OF BEAUTY PRODUCT ADVERTISEMENTS IN SHAPING SOCIETAL PERCEPTIONS - widiastuti Widiastuti (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
Through television broadcasts, electronic and online platforms, as well as printed media, the public can readily access information about a variety of brands, presented through captivating images and compelling text. Undeniably, the most potent force in advertising lies in the utilization of language that can transform the perceptions and viewpoints of potential consumer groups. This study's primary objective is to deconstruct the advertising strategies employed by two competing beauty product brands, aiming to win over the favor of potential customers. While prior research has delved into the ideological aspects of beauty advertisements using Critical Discourse Analysis, there remains a scarcity of studies that undertake a comparative analysis of local and international beauty products. To accumulate data, this study closely examined the promotional materials of two rival beauty product brands, they are: Scarlett and Skintific which is prominently featured on the online platform YouTube. The analysis adopted the Critical Discourse Analysis framework developed by Norman Fairclough, encompassing three interconnected dimensions: the textual content itself, the underlying discourse practices, and the broader socio-cultural context. The outcomes unveiled that the textual components within the advertisements were meticulously constructed to evoke persuasion and resonate with the emotions of potential buyers. Additionally, these textual elements contributed to amplifying existing realities while also shaping specific narratives within society, ultimately guiding the advertisements toward the ultimate goal of invoking empathy from potential consumers